ANALYSIS OF CRITICAL THINKING ABILITY IN LIVEWORKHEET ASSISTED COOPERATIVE LEARNING SETTINGS - Nopia Rizki; Baiduri Baiduri; Siti Inganah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The ability to think critically in mathematics is one of the thinking skills needed by students to obtain a problem-solving procedure and to find logical results, especially when facing developments in the 21st century. One of them is by implementing cooperative learning assisted by liveworksheets. The purpose of this study was to determine students' critical thinking skills in the implementation of cooperative learning assisted by liveworksheets. This research uses descriptive research with a qualitative approach. The subjects of the study were 30 students in class VIII-I. Research instruments in the form of lesson plans, observation sheets, tests, and interviews. Data collection techniques using observation, tests, and interviews. The results showed that the student's critical thinking skills were mostly 72.36%, including the high category and the level of students' activeness in learning mathematics was 82.1%